Critiquing prescriptions of place and belonging in neoliberal post-apartheid Cape Town: An ethnography on the politics of abjection in language, policy, and practice - Michaels, Angelique Olivia (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.